Photosynthetic responses of seagrass in Changuu Island (Zanzibar Archipelago, Tanzania) during a nutrient enrichment and macrofauna exclusion experiment - Agustín Moreira-Saporiti; Mirta Teichberg; Aoife O extquotesingleSullivan (PANGAEA, 2026)
Seagrass photosynthetic responses (alpha, Ek and ETRmax) were measured during a nutrient enrichment and macrofauna exclusion experiment. A total of 24 plots were set up parallel to the shore, with presence of two seagrass species (Thalassodendron ciliatum and Thalassia hemprichii) in each plot. The experiment was the factorial combination of two treatments: macrofauna exclusion using cages (three levels: open, closed and uncaged) and nutrient enrichment using garden NPK fertilizer (two levels: ambient and enriched). Each treatment combination was replicated four times. Exclusion treatment simulates the consequences for the food web of losing a top predators and macrograzers. Nutrient enrichment was simulated by issuing nitrogen-phosphorus-potassium (NPK) [15:9:20] fertilizer pellets. NPK fertilizer fast release pellets were packed into cotton tubes and then into a perforated plastic tubes to simulate slow release of nutrients. The tubes were buried half-way into the sediment to ensure enrichment of both the water column and the sediment. Data was collected between July 19th and September 20th of 2017 in three sampling times. Day 20 (09.08.2017), Day 38 (31.08.2017) and Day 63 (19.09.2017). Data collection and experiment took place in Changuu Island (Zanzibar Archipelago, Tanzania; 0611 extquotesingleS, 3916 extquotesingleE). Changuu Island is located 3 km from Stone Town, Zanzibar extquotesingles busiest town. Changuu remains relatively unaffected by nutrient runoff pollution. The study area is characterised by a fringing reef around a multi-specific seagrass ecosystem. The substrate is primarily carbonate sediment. Average water depth is approximately 30 cm at Spring Low and 5 m at Spring high tide with an average depth of 2 m. Seagrass photosynthetic traits were measured to understand the photosynthetic responses of two seagrass species present in Changuu Island to the nutrient enrichment and macrofauna exclusion treatments. To determine the photosynthetic responses of the seagrass plants, their photosynthetic performance was measured through rapid light response curves (RLCs) generated by a Diving PAM chlorophyll fluorometer (Walz, Germany). RLCs were performed above the meristem of the second leaf of one plant per treatment plot for T. hemprichii and T. ciliatum. The basal portion of the leaf was chosen since it represents similar distances from the surface (and thus from the light source) among plants with different leaf lengths, thus minimizing variability within plants and species. A clip was attached to the leaf and to hold the optical cable of the PAM at 3 mm distance from the tissue and to dark adapt the tissue for 5 min prior to measurement. Leaves were kept in a laboratory tray with ambient seawater during dark adaptation and through the measurements. The first quantum yield measurement was performed in the absence of actinic light (dark-adapted effective quantum yield), after which the RLC consisted of 8 saturating light pulses (separated by 30-s intervals), increasing the photosynthetic active radiation (PAR) between pulses until 819 μmol photons m–2 s–1. The effective quantum yield (ΔF/Fm extquotesingle) was measured in each interval. From the RLC, light saturation coefficient (Ek) and the slope of the light limited part of the curve (Alpha) were calculated using the package "Phytotools" (Silsbe and Malkin, 2015) following the model of Jassby and Platt (1976) under the R software (R Core Team, 2019). The maximum light utilization efficiency or maximum quantum yield of PSII was calculated following equation by Genty et al. (1989) [Fv/Fm = (Fm-Fo)/Fm], where Fm is the maximum dark-adapted fluorescence and Fo is the minimal fluorescence from a dark-adapted sample. The relative electron transport rate (rETR) was calculated for each step of the curve following the equation by Sakshaug et al. (1997), [rETR = (Fm extquotesingle-F extquotesingle/Fm extquotesingle)_*(PAR/2)], where Fm extquotesingle is the light adapted maximum fluorescence and F extquotesingle the fluorescence yield at a particular light level. From the rETR values, maximum rETR (rETRmax) was estimated as the inflection point of the fitted rETR curve.